Justification and excuse in international law : concept and theory of general defences - Paddeu, Federica, 1982- (Cambridge : Cambridge University Press, 2018)
The defences available to an agent accused of wrongdoing can be considered as justifications (which render acts lawful) or excuses (which shield the agent from the legal consequences of the wrongful act). This distinction is familiar to many domestic legal systems, and tracks analogous notions in moral philosophy and ordinary language. Nevertheless, it remains contested in some domestic jurisdictions where it is often argued that the distinction is purely theoretical and has no consequences in practice. In international law too the distinction has been fraught with controversy, though there are increasing calls for its recognition. This book is the first to comprehensively and thoroughly examine the distinction and its relevance to the international legal order. Combining an analysis of State practice, historical, doctrinal and theoretical developments, the book shows that the distinction is not only possible in international law but that it is also one that would have important practical implications.
Machine generated contents note: Introduction; 1. Justification and excuse in international law; 2. Consent; 3. Self-defence; 4. Countermeasures; 5. Force majeure; 5. State of necessity; 6. Distress; Conclusion.
Title from publisher's bibliographic system (viewed on 19 Jan 2018).
Keywords: Government liability (International law); International obligations; Self-defense (International law); Necessity (Law)